THE ROLE AND ESSENCE OF ’POSITIONAL AND METRIC PROBLEMS’ IN PERSPECTIVE - Mamarajabova Shamsiqamar Nishon kizi (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Abstract: This article examines the theoretical and practical significance of "Positional and Metric Problems" within the science of perspective. Positional problems focus on the mutual intersection, belonging, and placement of geometric elements (points, lines, and planes) on a perspective plane, while metric problems deal with determining the actual dimensions, distances, angles, and natural shapes of objects depicted in a distorted perspective view. The study analyzes the algorithmic approach to solving these problems, which forms the core of descriptive geometry and architectural drawing. The integration of these classical problems with modern computer-aided design (CAD) systems is also discussed, highlighting their necessity in developing spatial reasoning for future engineers and architects.